A modified guar gum and its preparation method and application
By sulfoethylation-oxidation treatment of guar gum, modified guar gum with high viscosity and good instantaneous properties was prepared, which solved the insufficient performance of existing sand fixing agents and achieved efficient sand fixing inhibition. Dust effect.
Patent Information
- Application Number
- CN202211740158.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-12-30
AI Technical Summary
The existing chemical sand fixing agent preparation methods are complex, with weak anti-shrinking ability, poor permeability, poor water retention, uneven cementing, low strength of the consolidation layer, poor durability of the consolidation layer, poor freezing resistance, and traditional sand fixing agents are difficult to degrade, resulting in sand fixing. Poor results and pollute the environment.
By reacting guar gum with sulfoacetylation reagent and oxidizing agent, sulfoethylated-oxidized guar gum is prepared to improve its viscosity, instant cold water soluble properties, permeability, water retention, and strength and toughness after film formation.
The anti-shrinkage ability, permeability, water retention and consolidation layer strength of the sand fixing dust suppressor are improved, and the problems of low sand fixing efficiency and environmental pollution are solved, and the environmentally friendly sand fixing and dust suppression effect is achieved.
Smart Images

Figure CN115894736B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical sand fixation, and specifically relates to modified guar gum and a preparation method and application thereof. Background Art
[0002] Desertification is a major global ecological and environmental problem facing mankind, which troubles the survival and development of human society. The ever-increasing sandstorms and the expansion of desertified land have made the ecological environment even worse, devouring the living space of mankind and causing great harm to the national economy and social development. Desertified areas and their bordering areas are often accompanied by a series of ecological problems such as strong winds and sand, surface drought and soil erosion.
[0003] The current methods of sand control mainly include mechanical sand fixation, plant sand fixation and chemical sand fixation. Mechanical sand fixation, such as setting up sand barriers and grass grids, is characterized by quick results, but the investment is large and it is not suitable for large-scale use; plant sand fixation mainly involves planting shelterbelts on the edge or hinterland of the desert or forming plant crusts on the sand surface to reduce the wind speed in the desert and prevent the desert from sanding, thereby achieving the purpose of sand fixation. However, rainfall in desert areas is scarce, and long-term precipitation is less than surface evaporation. Therefore, in a sense, the transpiration of water brought about by the growth of sand-fixing plants accelerates the decline of groundwater levels. When the groundwater level drops to a certain depth, sand-fixing plants will also die; for places with harsh natural conditions, severe sand damage and the need for local rapid sand fixation, plant sand fixation is difficult to play a role in a short period of time, and may even be blown away by wind and sand. Chemical sand fixation is to use diluted chemical substances with certain cementing properties to spray on the surface of loose flowing sand. Water quickly penetrates into the sand layer, while chemical cementing substances are retained in the gaps of sand layers of a certain thickness, cementing single grains of sand into a protective layer, isolating the direct contact between airflow (wind) and the loose sand surface, thereby preventing wind erosion. Sand fixation agents generally should have good permeability and cementing properties. After spraying, they can quickly penetrate into the surface of sand dunes and bond sand particles to form a firmer crust layer, which can effectively consolidate the surface of sand dunes and prevent sand dunes from flowing. The advantages of chemical sand fixation technology are low cost, quick effect, simple construction, rapid improvement of desertified land, obvious water collection and moisture retention, temperature increase, improvement of soil structure, promotion of plant growth, inhibition of salt accumulation on the surface of saline soil, etc. At the same time, they can increase the organic matter content in sand, improve soil and be biodegradable, creating good water and soil conditions for plant growth. Therefore, chemical sand fixation agents are widely used because of their sand fixation and dust prevention effects.
[0004] Chemical sand fixation uses diluted chemical substances with certain cementing properties to spray on the surface of loose mobile sand. Water quickly penetrates into the sand layer, while chemical cementing substances are retained in the gaps of sand layers of a certain thickness (1~5 cm), cementing single grains of sand into a protective layer. The sand-fixing materials used in traditional sand-fixing agents include emulsified asphalt, phenolic resin, urea-formaldehyde resin, polyacrylamide, styrene-butadiene latex and polyurethane. Although they can achieve the purpose of windbreak and sand fixation, the existing sand-fixing agents have the disadvantages of complex preparation methods, weak anti-scouring ability, poor permeability, poor water retention, uneven cementation, low strength of the consolidation layer, poor durability of the consolidation layer, poor frost resistance, and low sand fixation efficiency, resulting in poor sand fixation effects. In addition, traditional sand-fixing agents are organic polymer products, which can achieve a certain purpose of sand fixation after use, but are difficult to degrade in nature, causing environmental pollution in desert areas, which to a certain extent limits the application of traditional chemical sand-fixing agents. Therefore, there is a great market demand for the development of a new type of sand-fixing agent that can solve the above problems.
[0005] Compared with traditional chemical sand-fixing agents, biological sand-fixing materials have greater practicality and development and promotion potential because they not only have good performance, but also reduce the consumption of resources and energy, and have ecological environmental coordination and compatibility. Guar gum, also known as guar gum, is a free-flowing powder ranging from white to slightly yellow. It is a natural polymer compound extracted from the plant guar bean. It belongs to natural linear galactomannan and has a very similar molecular structure to cellulose. It is rich in sources, low in price, easy to biodegrade, easy to modify, and no pollution to the environment. Although guar gum has good water solubility and thickening properties, its application is greatly limited due to its own shortcomings such as slow dissolution in cold water, more impurities, unstable viscosity, and poor storage stability. Summary of the invention
[0006] In order to improve the above technical problems, the present invention provides a method for preparing modified guar gum, comprising the following steps: reacting guar gum emulsion with a sulfonylating agent in the presence of an alkali to obtain sulfoethylated guar gum; and then reacting the emulsion with an oxidant to obtain sulfoethylated-oxidized modified guar gum.
[0007] According to the technical solution of the present invention, the preparation method comprises the following steps:
[0008] S1: preparing guar gum emulsion: mixing guar gum with a solvent to obtain guar gum emulsion;
[0009] S2: sulfoethylation reaction: the guar gum emulsion obtained in step S1 is first mixed with a base, and then mixed with a sulfoethylation agent to react to obtain sulfoethylated guar gum;
[0010] S3: Oxidation reaction: After the sulfoethylation reaction is completed, the pH is adjusted to 5-8 with an inorganic acid solution, and then mixed with an oxidant to react to obtain sulfoethylated-oxidized guar gum.
[0011] According to the technical solution of the present invention, in step S1, the molecular weight of the guar gum is 800000-1600000. The solvent is, for example, ethanol.
[0012] According to the technical solution of the present invention, the concentration of the guar gum emulsion in step S1 is 0.1-1 g / mL, for example, 0.2 g / mL, 0.3 g / mL, 0.4 g / mL, 0.5 g / mL.
[0013] According to the technical solution of the present invention, in step S2, the guar gum emulsion is mixed with the alkali and reacted for a period of time, the reaction temperature is, for example, 30-40°C, and the heating time is, for example, 10-120 min; after reacting with the alkali for a period of time, it is mixed with the sulfonylation agent for reaction, the reaction temperature is, for example, 50-80°C; the heating time is, for example, 60-240 min.
[0014] According to the technical solution of the present invention, the base in step S2 can be an inorganic base, such as sodium hydroxide.
[0015] According to the technical solution of the present invention, in step S2, alkali is added to adjust the pH of the guar gum emulsion to 10-13, preferably 10-12.
[0016] According to the technical solution of the present invention, in step S2, the sulfoethylating agent is, for example, one of: sodium 2-chloroethylsulfonate, 2-chloroethylsulfonic acid, sodium 2-bromoethylsulfonate, and 2-bromoethylsulfonic acid.
[0017] According to the technical solution of the present invention, in the above preparation method, 50 parts of guar gum, 10-30 parts of sulfonylating agent, and 0.1-2 parts of oxidant are used by weight.
[0018] According to the technical solution of the present invention, the sulfonylation agent can be 10 parts, 15 parts, 20 parts, 25 parts, 28 parts, 30 parts; preferably 20 parts.
[0019] According to the technical solution of the present invention, in step S3, the oxidant is hydrogen peroxide or peracetic acid, preferably hydrogen peroxide.
[0020] According to the technical solution of the present invention, in step S3, the inorganic acid is, for example, a hydrochloric acid solution or a sulfuric acid solution.
[0021] According to the technical solution of the present invention, the viscosity of the product obtained in step S3 is 500-3000 mPa•s.
[0022] According to the technical solution of the present invention, the preparation method further comprises S4: post-treatment: concentrating, centrifuging, washing with ethanol, drying, and then crushing and sieving the mixture to obtain modified guar gum.
[0023] According to the technical solution of the present invention, in step S4, the drying method is air flow drying, drum drying or spray drying.
[0024] According to the technical solution of the present invention, the drying method is preferably drum drying, and the drum speed is 20-50 rpm.
[0025] According to the technical solution of the present invention, the preparation method specifically comprises the following steps:
[0026] S1: Preparation of guar gum emulsion: dissolving guar gum in ethanol to prepare guar gum emulsion;
[0027] S2: Sulfonation reaction: adding sodium hydroxide powder to the guar gum emulsion in step S1, adjusting the pH of the guar gum emulsion to 10-12, and heating the reaction; then adding sodium 2-chloroethylsulfonate, and continuing to heat the reaction;
[0028] S3: Oxidation reaction: After the sulfoethylation reaction is completed, the pH is adjusted to 5-8 with an inorganic acid solution, an oxidant is added, and the reaction is heated to prepare a mixture of sulfoethylated and oxidized guar gum;
[0029] S4: Post-treatment: The mixture is concentrated, centrifuged, washed with ethanol, dried, crushed and sieved to obtain modified guar gum.
[0030] The invention also provides modified guar gum prepared by the method.
[0031] According to the technical solution of the present invention, the modified guar gum is sulfoethylated-oxidized guar gum. The degree of substitution of the sulfoethylated guar gum is, for example, 0.08-0.8, and the degree of substitution of the oxidized guar gum is, for example, 0.01-0.2.
[0032] The present invention also provides application of the modified guar gum, which is used for sand fixation and dust suppression.
[0033] The present invention also provides a sand-fixing and dust-suppressing agent, which comprises the modified guar gum of the present invention.
[0034] Beneficial effects of the present invention
[0035] 1) The present invention introduces sulfoethyl groups into guar gum molecules and oxidizes the guar gum, thereby increasing its viscosity, cold water solubility, permeability, water retention, strength and toughness after film formation.
[0036] 2) The modified guar gum of the present invention can be used as a film-forming agent and a binder for sand fixation and dust suppression, so as to solve the problems of weak anti-scouring ability, poor permeability, poor water retention, uneven bonding, low strength of the consolidation layer, poor durability of the consolidation layer, poor frost resistance, and low sand fixation efficiency during the use of the existing desert sand fixation and dust suppression agents.
[0037] 3) The viscosity of the product of the present invention is suitable and can be adjusted according to needs. The process operation is simple and easy to industrialize.
[0038] 4) The cold water instant guar gum has low preparation cost and simple process. After being used in the sand-fixing and dust-suppressing agent, it can be naturally degraded and is pollution-free. It is an environmentally friendly sand-fixing and dust-suppressing agent. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Attached Figure 1 This is a schematic diagram of the modified guar gum product prepared in Example 1.
[0040] Attached Figure 2 This is a schematic diagram of the modified guar gum product prepared in Example 2. DETAILED DESCRIPTION
[0041] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0042] Example 1
[0043] 1) Preparation of guar gum emulsion: first, 200 parts by weight of ethanol were placed in a reaction kettle, a stirrer was started, and 50 parts by weight of guar gum were added to prepare a guar gum emulsion;
[0044] 2) Sulfonation reaction: add sodium hydroxide powder to the guar gum emulsion to adjust the pH to 11, react at 35 °C for 20 min; then continue to heat to 55 °C, add 10 parts of sodium 2-chloroethyl sulfonate, and react for 100 min;
[0045] 3) Oxidation reaction: add hydrochloric acid solution to adjust pH=8.0, then add 1.8 parts by weight of hydrogen peroxide (30%), and react for 100 minutes;
[0046] 4) Post-treatment: The mixture is concentrated and centrifuged, washed with 10 parts by weight of 95% ethanol, drum dried at a pressure of about 0.3-0.5 MPa and a rotation speed of about 20-50 rpm, and then crushed and sieved to obtain cold water-soluble sulfoethyl-oxidized guar gum (the degree of substitution of the sulfoethylation reaction is 0.17, and the degree of substitution of the oxidation reaction is 0.015).
[0047] Example 2
[0048] Guar gum emulsion slurry preparation: firstly, 200 parts by weight of ethanol are placed in a reaction kettle, a stirrer is started, and 50 parts by weight of guar gum are added to prepare a guar gum emulsion;
[0049] Sulfoethylation reaction: sodium hydroxide powder was added to the guar gum emulsion to adjust the pH to 11, and the reaction was carried out at 35°C for 20 min; the temperature was raised to 55°C, 15 parts by weight of sodium 2-chloroethylsulfonate was added, and the reaction was carried out for 100 min;
[0050] Oxidation reaction: add hydrochloric acid solution to adjust pH=8.0, then add 1.5 parts by weight of hydrogen peroxide (30%), and react for 100 minutes;
[0051] Post-treatment: The mixture was concentrated and centrifuged, washed with 10 parts by weight of 95% ethanol, drum dried at a pressure of 0.3-0.5 MPa and a rotation speed of 20-50 rpm, and then crushed and sieved to obtain cold water-soluble sulfoethyl-oxidized guar gum (the degree of substitution of the sulfoethylation reaction is 0.25, and the degree of substitution of the oxidation reaction is 0.013).
[0052] Example 3
[0053] Preparation of guar gum emulsion: firstly, 200 parts by weight of ethanol were placed in a reaction kettle, a stirrer was started, and 50 parts of guar gum were added to prepare guar gum emulsion;
[0054] Sulfoethylation reaction: sodium hydroxide powder was added to the guar gum emulsion to adjust the pH to 11, and the mixture was reacted at 35°C for 20 min; the temperature was further raised to 55°C, and 20 parts by weight of sodium 2-chloroethylsulfonate was added and the mixture was reacted for 100 min;
[0055] Oxidation reaction: add hydrochloric acid solution to adjust pH=8.0, then add 1.2 parts by weight of hydrogen peroxide (30%), and react for 100 minutes;
[0056] Post-treatment: The mixture was concentrated and centrifuged, washed with 10 parts by weight of 95% ethanol, drum dried at a pressure of 0.3-0.5 MPa and a rotation speed of 20-50 rpm, and then crushed and sieved to obtain cold water-soluble sulfoethyl-oxidized guar gum (the degree of substitution of the sulfoethylation reaction is 0.36, and the degree of substitution of the oxidation reaction is 0.01).
[0057] Example 4
[0058] Preparation of guar gum emulsion: firstly, 200 parts by weight of ethanol were placed in a reaction kettle, a stirrer was started, and 50 parts of guar gum were added to prepare guar gum emulsion;
[0059] Sulfoethylation reaction: sodium hydroxide powder was added to the guar gum emulsion to adjust the pH to 11, and the reaction was carried out at 35°C for 20 min; the temperature was further raised to 55°C, 25 parts by weight of sodium 2-chloroethylsulfonate was added, and the reaction was carried out for 100 min;
[0060] Oxidation reaction: add hydrochloric acid solution to adjust pH=8.0, then add 0.8 parts by weight of hydrogen peroxide (30%), and react for 100 minutes;
[0061] Post-treatment: The mixture was concentrated and centrifuged, washed with 10 parts by weight of 95% ethanol, drum dried at a pressure of 0.3-0.5 MPa and a rotation speed of 20-45 rpm, and then crushed and sieved to obtain cold water-soluble sulfoethyl-oxidized guar gum (the degree of substitution of the sulfoethylation reaction is 0.44, and the degree of substitution of the oxidation reaction is 0.007).
[0062] Example 5
[0063] Preparation of guar gum emulsion: firstly, 200 parts by weight of ethanol were placed in a reaction kettle, a stirrer was started, and 50 parts of guar gum were added to prepare guar gum emulsion;
[0064] Sulfoethylation reaction: sodium hydroxide powder was added to the guar gum emulsion to adjust the pH to 11, and the reaction was carried out at 35°C for 20 min; the temperature was further raised to 55°C, 28 parts by weight of sodium 2-chloroethylsulfonate was added, and the reaction was carried out for 100 min;
[0065] Oxidation reaction: add hydrochloric acid solution to adjust pH=8.0, then add 0.5 parts by weight of hydrogen peroxide (30%), and react for 100 minutes;
[0066] Post-treatment: The mixture was concentrated and centrifuged, washed with 10 parts by weight of 95% ethanol, drum dried at a pressure of 0.3-0.5 MPa and a rotation speed of 20-50 rpm, and then crushed and sieved to obtain cold water-soluble sulfoethyl-oxidized guar gum (the degree of substitution of the sulfoethylation reaction is 0.51, and the degree of substitution of the oxidation reaction is 0.004).
[0067] Comparative Example 1
[0068] Preparation of guar gum emulsion: firstly, 200 parts by weight of ethanol were placed in a reaction kettle, a stirrer was started, and 50 parts of guar gum were added to prepare guar gum emulsion;
[0069] Sulfoethylation reaction: add sodium hydroxide powder to the guar gum emulsion to adjust the pH to 11, react at 35 °C for 20 min; continue to heat to 55 °C, add 10 parts of sodium 2-chloroethyl sulfonate, and react for 100 min;
[0070] Post-treatment: The mixture was concentrated and centrifuged, washed with 10 parts by weight of 95% ethanol, drum dried at a pressure of 0.3-0.5 MPa and a rotation speed of 20-50 rpm, and then crushed and sieved to obtain modified guar gum (the degree of substitution of the sulfoethylation reaction was 0.17).
[0071] Comparative Example 2
[0072] Preparation of guar gum emulsion: firstly, 200 parts by weight of ethanol were placed in a reaction kettle, a stirrer was started, and 50 parts of guar gum were added to prepare guar gum emulsion;
[0073] Oxidation reaction: add sodium hydroxide to the guar gum emulsion to adjust the pH to 8, react at 35°C for 20 min; then continue to heat to 55°C, add 2 parts by weight of hydrogen peroxide (30%), and react for 100 min;
[0074] Post-treatment: The mixture was concentrated and centrifuged, washed with 10 parts by weight of 95% ethanol, drum dried at a pressure of 0.3-0.5 MPa and a rotation speed of 20-50 rpm, and then crushed and sieved to obtain modified guar gum (the degree of substitution of the oxidation reaction was 0.018).
[0075] Application Examples
[0076] 1 g of the modified guar gum prepared in Examples 1-6 and Comparative Examples 1-3 was weighed and dissolved in 99 g of water and stirred for 30 min, and then placed in a 25° C. water bath and kept warm for 20 min to prepare a sample solution.
[0077] Viscosity determination:
[0078] The viscosity of the above sample solution was measured using a DV2TLVTJ0 viscometer, rotor No. 0, and a rotation speed of 60 r / min. The viscosity measurement standard was determined in accordance with Part 1 of the Railway Industry Standard of the People's Republic of China TB / T 3210.1-2020 Technical Conditions for Dust Suppression in Railway Coal Transportation.
[0079] Determination of pH value:
[0080] (1) Soak the glass electrode according to the instructions of the acidometer. For the same sample, select two standard buffer solutions with similar pH values to calibrate the acidometer.
[0081] (2) Place the beaker containing the sample solution in a constant temperature bath at 25±1℃. After the temperature reaches a stable equilibrium, rinse the glass electrode with distilled water and wipe it dry. Then wash the electrode with the sample solution and insert it into the sample for measurement.
[0082] (3) In the measurement of three consecutive samples, if the difference in pH values of the three samples is greater than 0.2, three new samples should be taken and measured again until the difference in pH values is no greater than 0.2.
[0083] (4) Take the arithmetic mean of the pH values of the three samples as the experimental result, and retain one decimal place.
[0084] Solid content determination:
[0085] (1) Take the mass of the sample solution as (10.0±0.1) g, accurate to 0.001 g, the experimental temperature as (105±2)°C, and the experimental time as (180±5) min. During the experiment, be careful to gently rotate the weighing bottle to completely flatten the sample solution to cover the entire bottom of the bottle.
[0086] (2) The experimental result is the average value of two parallel samples. If the difference between the two parallel samples (relative to the average value) is greater than 2%, the experiment needs to be repeated.
[0087] Determination of cured layer thickness
[0088] Select sand samples with mesh sizes of 50 to 100, dry them in an oven at (50±2)℃ for 300 min to remove moisture, and place them in an environment with a temperature of (20±5)℃ and a humidity of ≤50% for 1 h. Take an appropriate amount of dried sand samples and place them in three (300mm x 210mm x 30mm) sturdy and non-deformable trays that have been weighed at a constant weight at the experimental temperature and have a mass of W, so that the surface of the sand layer is flush with the tray. Place the three trays at 2.2 L / m 2 Spray the above sample solutions respectively, place them in an ambient temperature of (20±5) ℃ and humidity ≤50 % for 1 h, then place them in an oven at (50±2) ℃ for 120 min, randomly select six locations of the solidified layer on sample 1, sample 2 and sample 3, and measure their thickness with a measuring tool. The thickness of the solidified layer of sample 1 is H1, the thickness of the solidified layer of sample 2 is H2, and the thickness of the solidified layer of sample 3 is H3. The average value is the thickness of the solidified layer.
[0089] Wind erosion rate determination
[0090] Select sand samples with mesh sizes of 50 to 100, dry them in an oven at (50±2)℃ for 300 min to remove moisture, and place them in an environment with a temperature of (20±5)℃ and a humidity of ≤50% for 1 h. Take an appropriate amount of dried sand samples and place them in three (300mm x 210mm x 30mm) sturdy and non-deformable trays that have been weighed at a constant weight at the experimental temperature and have a mass of W, so that the surface of the sand layer is flush with the tray. Place the three trays at 2.2 L / m 2Spray the sample solution separately, place it in an oven at (20±5)℃ and humidity ≤50% for 1 hour, place it in an oven at (50±2)℃ for 120 minutes, and weigh it separately. The mass of the sand and the tray is W1. Put the prepared sample into a wind tunnel, and erode it for 30 minutes at a wind speed of (10.0±0.2) m / s on the surface of the sand layer, then erode it for 20 minutes at a wind speed of (15.0±0.2) m / s on the surface of the sand layer, and then erode it for 10 minutes at a wind speed of (30.0±0.2) m / s on the surface of the sand layer. Finally, weigh them separately. The mass of the remaining sand and the tray is W2. Then calculate the wind erosion rate of the sample according to the following formula;
[0091] Where:
[0092] E——sample wind erosion rate;
[0093] W——the mass of the pallet;
[0094] W1 – the mass of sand and tray before erosion;
[0095] W2 – Mass of sand and pallet after wind erosion.
[0096] The wind erosion rate of sample solution sample 1 is E1, the wind erosion rate of sample solution sample 2 is E2, and the wind erosion rate of sample solution sample 3 is E3, and their average value is taken.
[0097] The test results are shown in Table 1.
[0098] Table 1
[0099]
[0100] The cold water quick solubility and insoluble matter of the modified guar gum samples are shown in Table 2.
[0101] Table 2
[0102]
[0103] The performance comparison results of modified guar gum are shown in Table 3.
[0104] Table 3
[0105]
[0106] It can be seen that the sulfoethylated-oxidized guar gum prepared by the method of the present invention is used as a film-forming agent and a binder for desert sand fixation and dust suppression, which increases the anti-scouring ability, permeability, water retention, toughness and other properties, and improves the strength of the consolidation layer and the sand fixation efficiency. All technical indicators of sand fixation and dust suppression meet the standard requirements.
[0107] The above is a description of the exemplary embodiments of the present invention. However, the protection scope of the present application is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A sand-fixing and dust-suppressing agent, characterized in that: The modified guar gum comprises modified guar gum, and the modified guar gum is prepared by the following preparation method: S1: preparing guar gum emulsion: mixing guar gum with ethanol to obtain guar gum emulsion; S2: sulfoethylation reaction: the guar gum emulsion obtained in step S1 is first mixed with a base to adjust the pH of the guar gum emulsion to 10-13, and then mixed with a sulfoethylation agent to react to obtain sulfoethylated guar gum; S3: Oxidation reaction: After the sulfoethylation reaction is completed, the pH is adjusted to 5-8 with an inorganic acid solution, and then mixed with an oxidant to react to obtain sulfoethylated-oxidized modified guar gum; Optionally, the preparation method further comprises S4: post-treatment: concentrating the mixture, centrifuging, washing with ethanol, drying, and then crushing and sieving to obtain modified guar gum; The sulfoethylating agent is one of: sodium 2-chloroethylsulfonate, 2-chloroethylsulfonic acid, sodium 2-bromoethylsulfonate, and 2-bromoethylsulfonic acid; The concentration of the guar gum emulsion is 0.1-0.5 g / mL, and the molecular weight of the guar gum is 80000-160000; The oxidant is hydrogen peroxide or peracetic acid; By weight, the reaction raw materials contain 50 parts of guar gum, 10-30 parts of sulfoethylating agent, and 0.1-2 parts of oxidant.
2. The sand-fixing and dust-suppressing agent according to claim 1, characterized in that: The sulfonylation agent is 10 parts, 15 parts, 20 parts, 25 parts, 28 parts, and 30 parts.
3. The sand-fixing and dust-suppressing agent according to claim 1 or 2, characterized in that: The inorganic acid is hydrochloric acid solution or sulfuric acid solution.
4. The sand-fixing and dust-suppressing agent according to claim 1 or 2, characterized in that: The base in step S2 is an inorganic base.
5. The sand-fixing and dust-suppressing agent according to claim 1 or 2, characterized in that: In step S3, the inorganic acid is a hydrochloric acid solution or a sulfuric acid solution.
6. The sand-fixing and dust-suppressing agent according to claim 1, characterized in that: The preparation method of the modified guar gum consists of the following steps: S1: Preparation of guar gum emulsion: dissolving guar gum in ethanol to prepare guar gum emulsion; S2: Sulfonation reaction: adding sodium hydroxide powder to the guar gum emulsion in step S1, adjusting the pH of the guar gum emulsion to 10-12, and heating the reaction; then adding sodium 2-chloroethylsulfonate, and continuing to heat the reaction; S3: Oxidation reaction: After the sulfoethylation reaction is completed, the pH is adjusted to 5-8 with an inorganic acid solution, an oxidant is added, and the reaction is heated to prepare a mixture of sulfoethylated and oxidized guar gum; S4: Post-treatment: The mixture is concentrated, centrifuged, washed with ethanol, dried, crushed and sieved to obtain modified guar gum.
7. The sand-fixing and dust-suppressing agent according to claim 6, characterized in that: The guar gum emulsion is mixed with alkali and reacted for a period of time, the reaction temperature is 30-40°C, and the heating time is 10-120 min; after reacting with the alkali for a period of time, it is mixed with sodium 2-chloroethylsulfonate for reaction, the reaction temperature is 50-80°C, and the heating time is 60-240 min.
8. The method for preparing the modified guar gum in the sand-fixing and dust-suppressing agent of claim 1, characterized in that: include: S1: preparing guar gum emulsion: mixing guar gum with ethanol to obtain guar gum emulsion; S2: sulfoethylation reaction: the guar gum emulsion obtained in step S1 is first mixed with a base to adjust the pH of the guar gum emulsion to 10-13, and then mixed with a sulfoethylation agent to react to obtain sulfoethylated guar gum; S3: Oxidation reaction: After the sulfoethylation reaction is completed, the pH is adjusted to 5-8 with an inorganic acid solution, and then mixed with an oxidant to react to obtain sulfoethylated-oxidized modified guar gum; Optionally, the preparation method further comprises S4: post-treatment: concentrating the mixture, centrifuging, washing with ethanol, drying, and then crushing and sieving to obtain modified guar gum; The sulfoethylating agent is one of: sodium 2-chloroethylsulfonate, 2-chloroethylsulfonic acid, sodium 2-bromoethylsulfonate, and 2-bromoethylsulfonic acid; The concentration of the guar gum emulsion is 0.1-0.5 g / mL, and the molecular weight of the guar gum is 80000-160000; The oxidant is hydrogen peroxide or peracetic acid; By weight, the reaction raw materials contain 50 parts of guar gum, 10-30 parts of sulfoethylating agent, and 0.1-2 parts of oxidant.
9. The modified guar gum obtained by the preparation method according to claim 8.
10. The modified guar gum according to claim 9, characterized in that The modified guar gum is sulfoethylated-oxidized guar gum, the substitution degree of sulfoethylated guar gum is 0.08-0.8, and the substitution degree of oxidized guar gum is 0.01-0.
2.
11. The use of the modified guar gum according to claim 9 or 10, characterized in that: Used to prepare sand-fixing and dust-suppressing agents.
Citation Information
Patent Citations
Composite modified guar and preparation method thereof
CN101974100A
Anionic guar gum and preparation method thereof
CN102093485A
Preparation method and application of modified guar gum for preparing reactive printing paste
CN113735986A
Carboxymethyl dihydroxypropyl modified guar gum as well as preparation method and application thereof
CN114149513A
